Combined Disruption of the Thoracic Spine and Costal Arch Fracture: An Indicator of a Severe Chest Trauma - Schulz-Drost, Stefan; Kloesel, Stephan; Kuehling, Jan Carsten; Ekkernkamp, Axel; Bakir, Mustafa Sinan (Diagnostics, 2022)
Blunt high-energy chest trauma is often associated with thoracic and abdominal organ injuries. Literature for a hyperextension-distraction mechanism resulting in a costal arch fracture combined with a thoracic spine fracture is sparse. A 65-year-old male suffered a fall from a height of six meters. Initial X-ray of the chest shows left-sided high-riding diaphragm and CT scan proves anterior cartilage fracture, posterolateral serial rib fractures, traumatic intercostal pulmonary hernia, avulsion of the diaphragm, and 7th thoracic vertebral fracture. An exploratory thoracotomy was performed and the rupture of the diaphragm, creating a two-cavity injury, had been re-fixed, the pulmonary hernia was closed, and locking plate osteosyntheses of the fractured ribs including the costal arch were performed. We generally recommend surgical therapy of the thorax to restore stability in this severe injury entity. The spine was fixed dorsally using a screw-rod system. In conclusion, this thoracovertebral injury entity is associated with high overall injury severity and life-threatening thoracoabdominal injuries. Since two-cavity traumata and particularly diaphragmatic injuries are often diagnosed delayed, injuries to the costal arch can act as an indicator of severe trauma. They should be detected through clinical examination and assessment of the trauma CT in the soft tissue window.
CRIS-Team Scopus Importer:2022-10-07
Keywords: costal arch fracture; indicator injury; intercostal hernia; severely injured; thoracic spine fracture